2022
DOI: 10.3389/fmars.2022.960746
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical features and modulation of digestive enzymes by environmental temperature in the greater amberjack, Seriola dumerili

Abstract: The study of fish digestive biochemistry is essential to understand factors that affect the net efficiency of food transformation and growth, and therefore aquaculture profitability. The aim of the present study was to assess the activity and functional characteristics of key digestive enzymes in juveniles of greater amberjack (Seriola dumerili), as well as the possible modulation of their relative importance by water temperature. For that, a combination of biochemical assays and substrate-SDS-PAGE were used. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 48 publications
(62 reference statements)
0
6
1
Order By: Relevance
“…In the upper GI regions, this distribution is mainly driven by the acidic conditions (luminal pH < 3), coupled with the high concentrations of host secretions (e.g. antimicrobial effectors, bile acids, pancreatic [5] and dissected guts of adult Drosophila [6], honeybee [7] and Seriola dumerilii [8]. The different gut regions are labelled in each figure.…”
Section: Anatomymentioning
confidence: 99%
See 2 more Smart Citations
“…In the upper GI regions, this distribution is mainly driven by the acidic conditions (luminal pH < 3), coupled with the high concentrations of host secretions (e.g. antimicrobial effectors, bile acids, pancreatic [5] and dissected guts of adult Drosophila [6], honeybee [7] and Seriola dumerilii [8]. The different gut regions are labelled in each figure.…”
Section: Anatomymentioning
confidence: 99%
“…pH, redox potential, oxygen availability, antimicrobial compounds) along the gastrointestinal (GI) tract are crucial regulators of microbial homeostasis, shaping the composition, density and colonization rate of gut microbiome across vertebrate and invertebrate taxa ( figure 1 a and table 1 ).
Figure 1 ( a ) Differential interference contrast microscopy (DIC) image of the body of C. elegans [ 5 ] and dissected guts of adult Drosophila [ 6 ], honeybee [ 7 ] and Seriola dumerilii [ 8 ]. The different gut regions are labelled in each figure.
…”
Section: Anatomymentioning
confidence: 99%
See 1 more Smart Citation
“…The study of fish digestive biochemistry is essential to understand factors that affect the net efficiency of food transformation and growth, and therefore aquaculture profitability (Navarro-Guillén et al, 2022) Information of exact enzyme activities, habit of animal as well as digestive process have significance in the formulation of suitable feed of any type of organism (Candiotto et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Greater amberjack is an economically important fish that is widely popular for its tasty meat, and it is also a major predator and inhabitant of artificial reefs such as coral reefs and shipwrecks, maintaining the structure and function of these ecosystems (Pereira et al, 2023). It has been widely reported that the growth, development, and physiology of greater amberjack were sensitive to the changes of water salinity, temperature, and seawater pressure (Barany et al, 2021; Navarro-Guillen et al, 2022; Peng et al, 2022; Liu et al, 2023; Ru et al, 2023). Comparative transcriptomic analyses showed that salinity alternations substantially disrupt tissue growth and development, energy metabolism, and immune responses in greater amberjack (Peng et al, 2022; Liu et al, 2023).…”
Section: Introductionmentioning
confidence: 99%